Biological network analysis and subnetwork extraction tool - Rodriguez, Danielle M. (Animo Repository, 2019)
Research has presented that when dealing with complex protein chains of various diseases, there is a large amount of proteins that interact with each other in different ways. Due to the complexity of the control mechanisms involved, and the large number of possible interactions, there is a great need for computer-assisted tools. The Biological Net Extranalysis is a tool that helps the user visualize a graph, extract a subnetwork containing the relationships that are significant in the network, and perform network analysis on the graph. ©2018 IEEE